2017
DOI: 10.1002/eco.1851
|View full text |Cite
|
Sign up to set email alerts
|

Estimating regional losses of soil water due to the conversion of agricultural land to forest in China's Loess Plateau

Abstract: Afforestation on the Chinese Loess Plateau (CLP) has been extensively implemented by the central government over the past decades to control soil erosion. The conversion of agricultural land to forest, however, has led to decreases in soil‐water storage (SWS), which may in turn limit tree growth and threaten the health of ecosystems in the region. This study estimated the regional patterns of losses of soil water (ΔSWS) following conversions across the CLP. Soil‐water content at 0–5.0 m was measured in 169 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 43 publications
1
32
2
1
Order By: Relevance
“…In the middle of the LP where precipitation is relatively abundant, high rates of soil water uptake by replanted forest contributed to the acceleration of soil desiccation range and intensity. Conversion of cropland to artificial forest has led to a considerable increase in vegetation coverage, but large‐scale vegetation restoration has had negative impacts on soil hydrological conditions (Chen et al, 2008; Wang et al, 2008; Jia et al, 2017b). To prevent the formation of soil desiccation and reduce the negative effects of replanted forests on the soil water budget, more information is needed about the effects of forest density, structure and species on soil water use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the middle of the LP where precipitation is relatively abundant, high rates of soil water uptake by replanted forest contributed to the acceleration of soil desiccation range and intensity. Conversion of cropland to artificial forest has led to a considerable increase in vegetation coverage, but large‐scale vegetation restoration has had negative impacts on soil hydrological conditions (Chen et al, 2008; Wang et al, 2008; Jia et al, 2017b). To prevent the formation of soil desiccation and reduce the negative effects of replanted forests on the soil water budget, more information is needed about the effects of forest density, structure and species on soil water use.…”
Section: Discussionmentioning
confidence: 99%
“…Between 2000 and 2008, the “Grain‐for‐Green” project has resulted in a 10.8% reduction in cropland area, and a 4.9 and 6.6% increase area of forestland and grassland in the LP, respectively (Lü et al, 2012). However, unsuitable vegetation restoration measures and poor land management have aggravated water scarcity and led to soil desiccation in deep soil layers (Li, 2001; Jia et al, 2017a, 2017b). The depth of depleted soil water sometimes exceeds 5 m because of the wide spread introduction of exotic plant species with deep root systems (e.g., Medicago sativa , Caragana korshinskii , Robinia pseudoacacia , and Pinus tabulaeformis ) (Li and Huang, 2008; Wang et al, 2009).…”
mentioning
confidence: 99%
“…Second, construction of the basic farmland and farmland infrastructure was enhanced to ensure grain production after large-scale cropland conversion [54]. Therefore, the changing rates of cropland are quite high in all sub-regions ( Figure 7).…”
Section: Differences Of Vegetation Dynamics Features Among Land Use Pmentioning
confidence: 99%
“…For example, Wang, Liu, Liu, and Zhang (2009) demonstrated that the depth of soil moisture depleted by alfalfa, shrub, and pine (common species chosen for revegetation) on the CLP reached 15.5, 22.4, and 21.5 m, respectively. Jia, Wang, Shao, Luo, and Zhang (2017) calculated that the mean annual soil moisture loss from 1 to 5-m depth increased at a rate of 16.2 mm/year after farmland conversion to forestland. Additionally, soil moisture dynamics in the shallow soils have been altered after vegetation restoration.…”
Section: Introductionmentioning
confidence: 99%